A186 HEPATIC STEATOSIS PREDICTS FIBROSIS IN LONG-TERM METHOTREXATE USE. (26th February 2020) - Tomaszewski, M; Dahiya, M; Mohajerani, A; Punja, H; Ko, H; Ramji, A
Abstract: Background: Methotrexate (MTX) is effective for dermatologic and rheumatologic conditions such as psoriasis (Ps), psoriatic arthritis (PsO) and rheumatoid arthritis (RA). Long-term MTX use may be complicated by hepatic fibrosis, although patient, disease factors and the mechanism remain unclear. Transient elastography (TE) is a non-invasive measure of hepatic fibrosis that is often used as surveillance in this patient population. Patients with Ps and PsO have higher rates of non-alcoholic fatty liver disease. The controlled attenuation parameter (CAP) measurement is a non-invasive test that correlates with histologic degree of steatosis. To our knowledge, no studies have evaluated hepatic steatosis via CAP scores in MTX use. Aims: To determine the prevalence of steatosis and significant fibrosis (F≥stage 2) in persons on MTX therapy and to determine the predictive factors for these events. Methods: A single centred retrospective cohort study was performed. Patients on >6 months of MTX for a dermatologic or rheumatologic disease who had undergone TE from January 2015 to September 2019 were included. Demographic variables, laboratory investigations, TE and CAP scores were collected. Multivariate analysis was performed to determine predictors of steatosis and fibrosis. Results: A total of 177 patients on methotrexate were included. Ps was the most frequent diagnosis (n=52) followed by RA (n=50) and PsO (n=38). Steatosis (CAP≥245 dB/m) was present in 73.9% of patients. Patients with steatosis had significantly more fibrosis and a higher BMI than those without steatosis (CAP<245 dB/m). Higher CAP score was correlated with increased lifetime dose of methotrexate by Pearson correlation analysis (r=0.48, p=0.001) (n=85 patients). Multivariate regression analysis revealed that diabetes mellitus (OR 10.5, 95% CI 1.38–80.60), hypertension (OR 4.97, 95% CI 1.66–14.84), and BMI> 30 (OR 10.1, 95% CI 1.88–37.14) were predictors of steatosis (CAP≥245 dB/m). Predictors of METAVIR≥F2 (TE≥8.0 kPa) by multivariate regression analysis included CAP score of ≥270 (OR 8.36, 95% CI 1.88–37.14), diabetes mellitus (OR 2.85, 95% CI 1.09–7.48), hypertension (OR 5.4, 95% CI 2.23–13.0), dyslipidemia (OR 3.71, 95% CI 1.50–9.18) and alcohol use (OR 3.06, 95% CI 1.2–7.49). Conclusions: In patients on MTX for rheumatologic and dermatologic diseases, hepatic steatosis was common and predicted significant fibrosis. Additionally, increasing MTX exposure is correlated with steatosis. Features of the metabolic syndrome including diabetes, hypertension or obesity were predictors of both steatosis and fibrosis (F≥2). Further study is needed to evaluate if steatosis is a mechanism by which fibrosis occurs in patients on MTX, or if it due to other patient factors. Funding Agencies: None